Sex difference in cerebral atherosclerotic stenosis in Chinese asymptomatic subjects - Xiangkun Tao; Renjie Qiao; Can Liu; Lu Guo; Jingcheng Li; Yulai Kang; Youdong Wei (Heliyon, 2023)
Background and purpose: Sex difference in cerebral atherosclerosis has been noted in previous studies, but the precise characteristics remain incompletely elucidated. This study aims to identify the sex difference in patients with asymptomatic cerebrovascular stenosis. Materials and methods: The image and clinical data of 1305 consecutive patients who had head and neck computed tomography angiography (CTA) were collected. Fifty hundred and seventy-three patients (287 males) with asymptomatic atherosclerotic stenosis in cerebral arteries were finally included. The stenosis number, distribution, severity and their changes with age were analyzed and compared between males and females. Simple linear regression was used to assess the change in lesions with age. Results: A total of 2097 stenoses were identified in 573 patients, males had more stenoses than females (3 [2, 5] vs 3 [2, 4], p=0.015). The number of stenoses in extracranial arteries was much higher in males (p = 0.001). Females had higher percentage of stenosis in anterior (89.6% vs 85.9%, p = 0.012) and intracranial arteries (63.3% vs 57.1%, p = 0.004) than males. Males had higher percentage of moderate-severe stenosis (5.1% vs 3.2%, p = 0.026). Age (OR = 1.67; 95% CI 1.24–2.25; p < 0.001) and hypertension (OR = 2.53; 95% CI 1.24–5.15; p = 0.01) were associated with moderate-severe stenosis. In patients over 50 years old, the number of stenoses increased by 1.03 per 10 years (p < 0.001), with 0.72 more stenoses in males (p = 0.003). Conclusions: Cerebral atherosclerotic stenosis was different between sexes regarding the distribution, severity and the change pattern with age, which underline the sex specific management in patients with cerebral atherosclerosis.